The Affecting Factors on Computer Based Test of National English Examination at SMAN 1 Raha - Nusi, Amelia Amanda; Nggawu, La Ode; Fatmawati, Wa Ode (Universitas Halu Oleo, 2021)
This study was conducted to investigate the factors that affect English national examination success in Computer Based Test (CBT) at SMAN 1 Raha. This study's research question was